2010
DOI: 10.1182/blood-2008-12-192591
|View full text |Cite
|
Sign up to set email alerts
|

CD137 agonist antibody prevents cancer recurrence: contribution of CD137 on both hematopoietic and nonhematopoietic cells

Abstract: Antigen-specific memory T cells (Tms) are essential in the immune surveillance of residual and metastatic tumors. Activation of Tms requires designing vaccines based on tumor rejection antigens, which are often not available to cancer patients. Therefore, it is desirable to have a general applicable approach to activate Tms without extensive knowledge of tumor antigens. Here, we report that activation of antigen-specific Tms could be achieved by the administration of agonistic anti-CD137 monoclonal antibody wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…Agonistic anti-CD137 mAb can expand Treg cells in vivo (our unpublished data). The expansion of Treg cells by agonistic anti-CD137 mAb is dependent upon IL-2 which is secreted by memory T cells (Zhu et al, 2007;Narazaki et al, 2010). Our unpublished results showed that Treg cells primed by anti-CD137 mAb have a higher ability to suppress the proliferation and cytokine production of CD4 + T cells.…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 49%
“…Agonistic anti-CD137 mAb can expand Treg cells in vivo (our unpublished data). The expansion of Treg cells by agonistic anti-CD137 mAb is dependent upon IL-2 which is secreted by memory T cells (Zhu et al, 2007;Narazaki et al, 2010). Our unpublished results showed that Treg cells primed by anti-CD137 mAb have a higher ability to suppress the proliferation and cytokine production of CD4 + T cells.…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 49%
“…Its ligand 4-1BBL is expressed on B cells, DCs, macrophages, activated T cells and endothelial cells [94][95][96]. Agonistic CD137 mAb stimulated the proliferation of CD4 and CD8 T cells, mainly CD8 CTL, increased cytokine production, prevent activation induced cell death [94,97] and in absence of cognate signals increases the memory T-cell expansion [98]. Large tumors in mice are eradicated with increased cytotoxic T-cell activity in poorly immunogenic Ag104A sarcoma and highly tumorigenic P815 mastocytoma using agonist CD137 mAb [99].…”
Section: Cd137(4-1bb)/cd137lmentioning
confidence: 99%
“…The amount of in vitrotranscribed mRNA for each chain was 2 lg/10 6 PBMCs. The sequences of the HLA-A2 restricted peptides used in our study are as follows: gp100 209M (IMDQVPFSV) and HBV [18][19][20][21][22][23][24][25][26][27] (FLPSDFFPSV).…”
Section: Tcr and Peptidesmentioning
confidence: 99%
“…5 To assess the stimulatory potential of DCs on 4-1BB-transduced cells, we produced autologous DCs from those patients and pulsed them with either the specific gp100 209 epitope or an irrelevant peptide (HBV [18][19][20][21][22][23][24][25][26][27] ). After coculture with transduced lymphocytes, we observed an increased IFN-g secretion by 4-1BB-transduced versus GFP-transduced cells (Fig.…”
Section: Improved Function Of 4-1bb-transduced Lymphocytes From Vaccimentioning
confidence: 99%
See 1 more Smart Citation